2010
DOI: 10.1248/bpb.33.1279
|View full text |Cite
|
Sign up to set email alerts
|

Decursin Prevents Cisplatin-Induced Apoptosis via the Enhancement of Antioxidant Enzymes in Human Renal Epithelial Cells

Abstract: Adverse effects, nephrotoxicity and hepatotoxicity, of anticancer drugs such as cisplatin have limited the usage for cancer therapy. Therefore, development or identification of supplement agents in anticancer drugs is attractive to reduce side effects and enhance antitumor activity. Here, we found that decursin isolated from Angelica gigas showed protective effects of cisplatin-induced damage in normal human primary renal epithelial cells (HRCs). We found that decursin significantly blocked cisplatin-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The free radical scavenging ability of decursin can be attributed to a significant reduction in the glutamate‐induced intracellular calcium levels in cortical cells via activation of the cellular antioxidative defense enzymes (Kang and Kim, ). Decursin also protects against cisplatin‐induced damage in normal human primary renal epithelial cells (HRCs) by modulating the activities of antioxidant enzymes such as superoxide dismutase, catalase and glutathione peroxidase (Kim et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The free radical scavenging ability of decursin can be attributed to a significant reduction in the glutamate‐induced intracellular calcium levels in cortical cells via activation of the cellular antioxidative defense enzymes (Kang and Kim, ). Decursin also protects against cisplatin‐induced damage in normal human primary renal epithelial cells (HRCs) by modulating the activities of antioxidant enzymes such as superoxide dismutase, catalase and glutathione peroxidase (Kim et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Angelica gigas , a medicinal plant that contains several biologically active compounds, has been used traditionally in Korea for the prevention of various diseases (Lee et al ., ; Han et al ., ). A coumarin compound, decursin, is abundant in A. gigas , and has been identified to exert beneficial effects against disease models such as cancer, oxidative stress and inflammation (Kim et al, ; Jiang et al ., ; Yang et al ., ). Several studies have reported that decursin inhibits extracellular signal‐regulated kinase activation, c‐Jun N ‐terminal kinase and the VEGF‐2 signaling pathway in several cancer types (Son et al ., ; Kim et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its major compound decursin exerted antitumor activity by apoptosis induction or angiogenesis inhibition in various cancer cells including prostate, bladder, and colon cancer, and leukemia [1214]. Also, our group reported that decursin has a protective effect on neurotoxicity and nephrotoxicity in normal cells via activation of antioxidative enzymes [15, 16] and also decursin-induced apoptosis through inhibition of STAT3 signaling pathway in multiple myeloma U266 cells [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Activation of the NF-κB signaling pathway is intimately related with MAPK activation (Tak & Firestein, 2001). It is crucial of MAPK that involved in the regulation of the proinflammatory mediators such as COX-2 (Kaminska, 2005;Kim, Jeong et al, 2010). Pharmacologic inhibitor of p38 and ERK and dominant-negative mutation of both proteins restrained not only NF-κB transactivation induced by Aβ but also the expression of COX-2 protein and PGE2 content (Jang & Surh, 2005).…”
mentioning
confidence: 99%